Effects of Maltodextrin on Sauropus androgynus Leaf Extract Characteristics - Yunita, Oeke; Nuniek Winantari, Agnes; Permana Sugiarto, Ricky; Sutanto Prayitna, Gunawan; Hwa, Lie (Indonesian Journal of Pharmacy, 2022)
Katuk (Sauropus androgynus) leaves have been traditionally used in Indonesia for increasing human breast milk production. In the previous research, katuk leaves have high moisture content, therefore katuk leaves extract were being prepared as spray dried S. androgynus extract. The freeze dried leaves were extracted with ultrasonic assisted extraction method using ethanol 80% as a solvent. Then, katuk extract was dried with spray drying method using maltodextrin as a drying aid. To improve the physical characteristics of this extract, it was mixed with mannitol, spray dried lactose, and crospovidone into S. androgynus extract powder. The results showed better physical characteristics, especially on moisture content and flow properties of powders. Metabolic profiles of all samples were analysed by thin layer chromatography (TLC) densitometry method, while the dried extract was dissolved in a suitable solvent and then spotted on GF254 and the plate was developed using a mixture of n-butanol:acetic acid:water (60:22:1.2). Based on TLC profiles, there are three different spots can be seen clearly at 366 nm on chromatogram of S. androgynus leaves, freeze dried leaves, spray dried leaves extract, and leaves extract powder. There is one spot (S3) at Rf 0.80 which is a stable chemical compound that is not affected by all factors in the entire process in S. androgynus extract powder formulations from extraction, drying, to formulation.